Calidad del sueño en una facultad de medicina de Lambayeque - Granados-Carrasco, Zaida (2013)
Background: Good sleep quality is important for university students to accomplish satisfactory academic performance. There is lack oflocal data on poor sleep quality frequency among faculty of medicine students. Objectives: To determine the frequency of poor sleepquality in students from a Faculty of Medicine. Design: Cross-sectional, descriptive study. Setting: Faculty of Medicine, UniversidadSanto Toribio de Mogrovejo (USAT), Chiclayo, Lambayeque, Peru. Participants: University students. Interventions: To students from allfour university schools -medicine, psychology, nursery and dentistry- the Pittsburg quality index scale validated in Spanish and in Peruwas applied. Main outcome measures: Frequency of poor sleeping quality by school and description of Pittsburg scale components.Results: Two hundred and forty-seven students were interviewed: 194 women (78.5%) and 53 men (21.5%). Median age was 20.04 ±2.53 years; there were 210 ‘poor sleepers’ (85%); the frequency of poor quality of sleepiness was as follows: medicine (89.5%), nursery(86.4%), dentistry (84.4%) and psychology (78.2%). Psychology students reported the highest use of hypnotics: 21.8%. Conclusions:At USAT Faculty of Medicine there was high frequency of poor sleep quality; the school of psychology reported the highest use ofhypnotics.